Could Hydroinfiltrators Made with Biochar Modify the Soil Microbiome? A Strategy of Soil Nature-Based Solution for Smart Agriculture - Azahara Navarro; Ana del Moral; Gabriel Delgado; Jesús Párraga; José Ángel Rufián; Raúl Rojano; Juan Manuel Martín-García (Applied Sciences)
Climate change negatively affects agriculture, causing desertification, salinisation, and drought. The biochar hydroinfiltrator (ES Patent No.: ES2793448 B2) is a device that increases the capture of rainwater or irrigation water for crops by increasing infiltration rates. Biochar, produced via biomass pyrolysis, has emerged as a promising agricultural amendment, as it helps to optimise moisture retention and improve soil structure, key aspects for boosting crop yields. There is growing interest in microorganisms’ plant-growth-promoting activity (PGP) by carrying out different activities considered growth promoters. The aim of the present study is to evaluate the use of a biochar hydroinfiltrator as a promoter of microbial activity when it is used in soil. Metagenomic analysis of soils with and without the device reveals that genera Bacillus and Sphingomonas became particularly enriched in soils with hydroinfiltrators. Also, in order to understand the interaction between the uses of biochar together with bacteria PGP, an in vitro test was carried out. Two microorganisms, previously selected for their characteristics as plant growth promoters, were inoculated in soils with and without biochar and they grew better after 15 to 30 days of inoculation, showing major CFU counts. This combined strategy—biochar hydroinfiltrator and PGP bacteria—offers an innovative, eco-friendly approach to sustainable agriculture, particularly under drought stress.